A voice without end: the role of David in psalms 3-14 - Witt, Andrew C. (Journal of Theological Interpretation Supplements, 2021)
Intro -- COVER Front -- Copyright Page -- Table of Contents -- Acknowledgments -- Chpter 1: The Figure of David and a Canonical Approach to Psalms 3-14 -- Chapter 2: The Speaking Persona(e) in the History of Interpretation -- Chapter 3: The Shaping of the Figure of David in the Psalms -- Chapter 4: The Figure of David in Psalms 3-6 -- Chapter 5: The Figure of David in Psalms 7-14 -- Chapter 6: Conclusions and Implications -- Bibliography -- Index.